2001
DOI: 10.1023/a:1017535728844
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Growing evidence suggests that intracellular vitamin D receptors are present in skeletal muscle tissue mediating vitamin D hormone response. The aim of the work reported here was to investigate the in situ expression of 1,25-dihydroxyvitamin D3 receptor in human skeletal muscle tissue. Intraoperative periarticular muscle biopsies were taken from 20 female orthopaedic patients (17 middle-aged and elderly patients receiving total hip arthroplasty due to osteoarthritis of the hip or an osteoporotic hip fracture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
124
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(129 citation statements)
references
References 30 publications
3
124
2
Order By: Relevance
“…Muscle tissues have highly specific nuclear receptors for 1,25-[OH]2D [8]. In the present study, we found improvement, by vitamin D, of type II fiber atrophy in stroke patients who had deficient levels of serum 25-OHD before the therapy.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Muscle tissues have highly specific nuclear receptors for 1,25-[OH]2D [8]. In the present study, we found improvement, by vitamin D, of type II fiber atrophy in stroke patients who had deficient levels of serum 25-OHD before the therapy.…”
Section: Discussionsupporting
confidence: 64%
“…In a randomized controlled trial, vitamin D reduced fractures within 8–12 weeks of the treatment, and this is consistent with the benefit on muscle strength [7]. Skeletal muscle is known to express specific receptors for 1,25-dihydroxyvitamin D (1,25-[OH]2D) [8]. …”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Vitamin D has been shown to increase skeletal muscle cell proliferation and muscle fiber size in vitro, 13,23 therefore it is biologically plausible for vitamin D serum levels to affect skeletal muscle efficiency through binding to the vitamin D receptor resulting in muscle growth. 13,23 This hypothesis may explain a potential contribution to the mechanism behind our observation of increased odds of vitamin D deficiency in women with fecal incontinence symptoms compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle is one such target organ 10 for vitamin D and VDR is reported to be expressed in human muscle 11 tissue [3,4]. Vitamin D deficiency has been associated with muscle 12 weakness and falls in humans [5,6].…”
Section: Introductionmentioning
confidence: 99%